2021
DOI: 10.1186/s12890-021-01619-y
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, placebo controlled, double blinded pilot superiority phase 2 trial to evaluate the effect of curcumin in moderate to severe asthmatics

Abstract: Background Curcumin, a derivative of the spice turmeric, has been adopted by Eastern medicine for centuries as an adjunct to treat several medical conditions (e.g., anorexia and arthritis) because of its well-established anti-inflammatory properties. Studies have shown that the use of curcumin in mice models has led to reduction in several inflammatory markers as well as key inflammatory pathway enzymes. As a result, studies in Western medicine have developed to determine if this recognized ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recent studies have demonstrated that curcumin can protect against Cd-induced damage by activating the anti-oxidative signaling pathway of Nrf2/ARE [ 7 , 50 ] Curcumin could reduce the neurotoxicity and tissue damage elicited by Cd and Pb by chelating these heavy metals. [ 42 , 51 ]. Due to its excellent activity of scavenging intracellular ROS activity, curcumin could be used as an effective antioxidant for the protection of polar ROS induced by heavy metals in the cytoplasm [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that curcumin can protect against Cd-induced damage by activating the anti-oxidative signaling pathway of Nrf2/ARE [ 7 , 50 ] Curcumin could reduce the neurotoxicity and tissue damage elicited by Cd and Pb by chelating these heavy metals. [ 42 , 51 ]. Due to its excellent activity of scavenging intracellular ROS activity, curcumin could be used as an effective antioxidant for the protection of polar ROS induced by heavy metals in the cytoplasm [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…55 There are plans to conduct clinical trials in order to evaluate effect of using curcumin in asthmatic patients. 56 Such studies would prove useful in assessing measurable effects of supplementing curcumin and its influence on asthma control in humans. Beneficial effect of omega-3 fatty acids is also mediated by free fatty acid receptor 4 (FFA4).…”
Section: Curcuminmentioning
confidence: 99%
“…In addition, administration of nutraceutical dietary supplements containing curcumin with resveratrol, soy phospholipids, zinc, selenium, and vitamin D in children with moderate to severe asthma was found to mitigate allergic airway inflammation as expressed by decreased fractional exhaled nitric oxide level [276]. Supplementation with high doses of curcumin (1500 mg twice daily) for 12 weeks is currently being investigated in a phase 2 clinical trial to evaluate the effect on moderate to severe asthma in adults; however, no data are available for review to date [277]. No side effects [263] Based on the findings from in vitro studies indicating the immunomodulatory activities of flavonoids, these polyphenolic compounds should also be considered as po-tentially effective preventive and therapeutic agents for asthma [251].…”
Section: Asthmamentioning
confidence: 99%